Frequency and molecular typing of nasal methicillin-resistant Staphylococcus aureus in admitted patients at a tertiary care hospital of Pakistan - Sultan, Aqib; Izhar, Mateen; Yaseen, Adnan; Tariq, Hira (Infectious Diseases Journal of Pakistan, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a prevalent pathogen responsible for infections in both community and healthcare environments. Nasal colonization with MRSA escalates the likelihood of severe infections and sepsis, especially among immunocompromised patients, contributing to morbidity and mortality within healthcare facilities. The aim of this study was to determine the frequency of community acquired MRSA (CA-MRSA) and hospital acquired MRSA (HA-MRSA) isolated from the nasal specimens of the admitted patients and to determine the frequency of PVL gene, SCCmec and spa types among CA-MRSA and HA-MRSA isolates. Material and Methods: In this prospective study at Shaikh Zayed Hospital, Lahore, 270 patients admitted to medical and surgical wards from 2020 to 2021 underwent nasal MRSA screening from admission to discharge. Standard microbiological tests identified isolates, which were then analyzed for PVL gene detection, SCCmec typing, and spa typing. Results: Out of 270 admitted patients screened for nasal colonization, 16 (5.9%) were colonized with CA-MRSA, while 13 (4.8%) acquired HA-MRSA. The prevalence of the PVL gene was 93.8% among CA-MRSA and 92.3% among HA-MRSA isolates. Spa typing identified t7358 as the predominant type in both CA-MRSA (75%) and HA-MRSA (100%) isolates. Regarding SCCmec typing, type IV was most prevalent among CA-MRSA (62.6%), while type III-B was most prevalent among HA-MRSA (46.1%) isolates. Conclusion: The study found a notable frequency of both CA-MRSA and HA-MRSA colonization among admitted patients. MRSA strains showed an elevated prevalence of the PVL gene. Additionally, SCCmec typing was more effective in characterizing CA-MRSA and HA-MRSA than spa typing. Keywords: Methicillin-resistant Staphylococcus aureus (MRSA), PVL gene, SCCmec typing, Spa typing